P025 Evaluation of endoplasmic reticulum stress in intestinal mucosa from patients with Crohn's disease. (15th January 2020) - Rodrigues, B; Pascoal, L B; Coope, A; Ayrizono, M L S; Camargo, M G; Velloso, L A; Fagundes, J J; Leal, R F
Abstract: Background: The endoplasmic reticulum (ER) is responsible for the synthesis and processing of secretory and membrane proteins. In some cases, proteins cannot reach their final conformation and they remain unfolded in the ER lumen. The accumulation of unfolded proteins leads to a state of stress in the ER (ER stress) that is considered toxic to the cells. As a result, cells may respond by driving the proteins to degradation, pausing the transcription process, or even inducing apoptosis. 1 ER stress has recently been linked to the exacerbation of the inflammatory process in the pathogenesis of Crohn's disease (CD). 2 Therefore, our aim was to evaluate the effect of a chemical inhibitor on the activation of ER stress pathways and its modulation of pro-inflammatory cytokines. Methods: After approval of a local Ethics Committee, biopsies of intestinal mucosa were collected by colonoscopy from patients with CD (CD group) and from patients without inflammatory bowel diseases (control group). Explant culture was performed to evaluate the occurrence of ER stress and was treated with a chemical ER stress inhibitor. Non-parametric tests were performed for statistical analysis adopting p < 0.05 as significant value. Results: Samples were collected from 10 patients with active CD (CDEIS ≥5) and six control patients. After cell culture, a significant difference was observed in the activation of the main ER stress pathway in the CD group when compared with control group. After treatment with a chemical inhibitor, there was significant decrease in the expression of genes responsible for the activation of ER stress. In addition, a decrease in the expression of inflammatory cytokines was observed after treatment. Conclusion: The use of a chemical inhibitor has been shown to be effective in significantly decreasing the activation of ER stress and to modulate the inflammation in CD. The activation of the main ER stress pathways may contribute to the inflammatory process in CD, and its blockade suggests a potential new target in the treatment of CD. References: Hotamisligil G.S. (2010) Endoplasmic reticulum stress and the inflammatory basis of metabolic disease. Cell 140, 900–917 Coope A, Pascoal LB, Botezelli JD, da Silva FAR, Ayrizono MLS, Rodrigues BL, Milanski M, Carvalho RB, Fagundes JJ, Velloso LA, Leal RF. (2019) ER stress activation in the intestinal mucosa but not in mesenteric adipose tissue is associated with inflammation in Crohn's disease patients. PLoS One . 26;14(9):e0223105. doi: 10.1371/journal.pone.0223105. eCollection 2019.